PENDIDIKAN KESEHATAN PENTINGNYA PEMBERIAN ASI EKSKLUSIF DI DESA PEJITALANG KECAMATAN MUMBULSARI KABUPATEN JEMBER - Trisna Pangestuning Tyas; Dinar Perbawati (Politeknik Kesehatan Kemenkes malang, 2022)
One of the efforts to reduce the IMR is to provide exclusive breastfeeding. Breast milk is the first natural food for babies which provides all the vitamins, minerals and nutrients a baby needs for growth in the first six months and no other food or fluids are needed. One of the causes of low breastfeeding in Indonesia is the lack of knowledge of pregnant women, families and communities about the importance of breastfeeding. The purpose of this activity is as a preventive effort in order to reduce infant mortality through exclusive breastfeeding. This Community Service activity was carried out in Pejitalang Village, Mumbulsari District, with a total of 25 pregnant and postpartum women. The target in this activity is all pregnant women and postpartum mothers in Pejitalang Village, Mumbulsari District. From the results of Community Service activities that have been carried out, it was found that the knowledge status of the mother understood 8 (32%) and the knowledge status of the mother did not understand 17 (68%). From the results of the analysis above, it can be concluded that most pregnant women and postpartum mothers in Pejitalang Village, Mumbulsari District do not understand the importance of exclusive breastfeeding for infants aged 0-6 months. Exclusive breastfeeding for infants aged 0-6 months